Investigação empírica sobre os efeitos da adoção do modelo do Prêmio Nacional da Qualidade na medição de desempenho - Oliveira, Gerusa Tinasi de (2006)
The changing basis of competition has emphasized the role of performance measurement as a strategic and competitive requirement for many organizations. In such context, companies from different countries have applied quality management methods as a manner to achieve organizational development. In Brazil, the National Quality Foundation (NQF) manages the Brazilian National Quality Award (BNQA), an award aimed at recognizing management excellence in organizations. In the same way, performance measurement has evolved in order to assess organizational performance, support strategy formulation and guide decision making. For performance measurement to contribute to competitiveness improvement, it is necessary the usage and management of performance information. In this sense, the objective of this study is to empirically investigate how companies which have adopted the Brazilian National Quality Award model for total quality management have altered their performance measurement systems. The research is based on the Lakatos investigation program, in an attempt to explain a perspective on paradigmatic change, like the changes in performance measurement emanating from the adoption of the BNQA management model. Hence, the empirical research here presented was designed and carried out by means of a combination of methods: documental research and multiple case studies. The main findings of the study, after the analysis and interpretation of the information gathered by both research methods, seem to indicate that the adoption of the Brazilian National Quality Award management model may be considered a catalyst for the changes in managerial practices and performance measurement of the studied companies.